Penguatan Inklusivitas Melalui Pengabdian Linguistik Terapan: Optimalisasi Keterampilan Lisan Bahasa Inggris Anak Panti Asuhan dengan Metode Simulasi Peran dalam Drama Interaktif - Putri, Rahmadila Eka; Nasution, Mutia; Agustina, Mahraini (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Enhancing inclusivity in English language instruction for children residing in orphanages necessitates pedagogical interventions that are not only linguistically responsive but also critically engaged with the participants’ socio-cultural realities. Structural constraints such as limited access to non-formal education, the absence of familial support systems, and the prevailing dominance of instructional paradigms within formal education have collectively contributed to the passive positioning of orphanage children, both within classroom practices and broader social structures that perpetuate marginalization. Their institutional status is often accompanied by social stigma, assumptions of dependency, a lack of affective reinforcement, and the absence of dialogic spaces essential for self-expression and active participation. This community service initiative employs interactive drama simulation as a core strategy, framed within the principles of experiential learning and critical applied linguistics. The pedagogical design seeks to cultivate a participatory, dialogic, and contextually grounded learning environment. Orphanage children are engaged not merely as learners, but as co-constructors of meaning, drawing upon their lived experiences through narrative, role-play, and performative expression. English, in this context, functions not solely as a communicative skill but as a medium of social emancipation and identity articulation. The program outcomes demonstrate significant improvements in communicative confidence, oral articulation, and critical language awareness. As such, this applied linguistic intervention illustrates the transformative potential of experience-based pedagogy in shifting power relations in education, enabling meaningful participation, and advancing a more dialogic, contextual, and socially empowering language learning framework. Abstrak Penguatan inklusivitas dalam pengajaran Bahasa Inggris bagi anak anak panti asuhan memerlukan intervensi pedagogis yang tidak hanya responsif secara linguistik, melainkan juga kritis terhadap realitas sosial peserta. Keterbatasan akses pendidikan non formal, ketiadaan dukungan keluarga inti, serta dominasi pendekatan instruksional dalam sistem pendidikan formal berkontribusi terhadap posisi pasif anak panti, tidak hanya dalam proses belajar, tetapi juga dalam struktur sosial yang kerap memarjinalkan mereka. Status sebagai anak panti sering kali disertai stigma ketergantungan sosial, minimnya dukungan afektif, dan kurangnya ruang dialogis yang menghambat ekspresi diri serta partisipasi aktif dalam pendidikan dan masyarakat. Pengabdian ini mengadopsi metode simulasi drama interaktif dalam kerangka experiential learning dan linguistik terapan kritis untuk menciptakan ruang belajar yang lebih partisipatif, dialogis, dan kontekstual. Anak anak panti tidak hanya dilibatkan sebagai peserta, tetapi juga sebagai aktor yang merekonstruksi pengalamannya melalui narasi, peran, dan ekspresi performatif. Penggunaan Bahasa Inggris dalam konteks ini tidak sekadar sebagai kompetensi komunikatif, melainkan sebagai sarana emansipasi sosial. Hasil kegiatan menunjukkan peningkatan keberanian berbicara, kemampuan artikulasi, serta kesadaran reflektif terhadap bahasa sebagai alat untuk menyuarakan identitas dan aspirasi. Dengan demikian, pengabdian linguistik terapan ini memperlihatkan bagaimana intervensi pedagogis berbasis pengalaman dapat menggeser relasi kuasa dalam pendidikan, membuka ruang partisipasi bermakna bagi anak panti, serta menjadi strategi transformatif bagi pengembangan pedagogi bahasa yang lebih dialogis, kontekstual, dan berorientasi pada pemberdayaan sosial.